B(C6F5)3‑Catalyzed C–Si/Si–H Cross-Metathesis of Hydrosilanes - Ma, Yuanhong; Zhang, Liang; Luo, Yong; Nishiura, Masayoshi; Hou, Zhaomin (Journal of the American Chemical Society, 2017)
The substituent redistribution of hydrosilanes on silicon through C–Si and Si–H bond cleavage and reformation is of great interest and importance, but this transformation is usually difficult to achieve in a selective fashion. By using electron-rich aromatic hydrosilanes, we have achieved for the first time the selective C–Si/Si–H bond homo- and cross-metathesis of a series of hydrosilanes in the presence of a boron catalyst B(C6F5)3. This protocol features simple reaction conditions, high chemoselectivity, wide substrate scope, and high functionality tolerance, offering a new pathway for the synthesis of multisubstituted functional silanes.